A beginner's guide to overlockers, sergers & coverlockers 50 lessons and 15 projects to get you started - Lubin, Clémentine (Tunbridge Wells, Kent Search Press, 2018)
Full of practical advice to help you master all the features and applications of your overlocker (serger) and coverlocker, you will learn how to handle your machine using its more complex features and will soon be finishing hems like a professional sewer.Hem and finish all your garments and accessories like a professional! This practical and comprehensive book helps you master all the functions and applications of your overlocker and coverlocker, from the simplest to the most complex. There are 50 beautifully photographed step-by-step lessons and 15 lovely projects to apply your knowledge and help you realize your sewing goals. You can make a dress, a T-shirt, a shoulder bag, a playsuit and more. There are 15 gorgeous projects to make including cushions, shoulder bags, soft toys and quilts. Full-size, fold-out patterns accompany the designs in addition to the 50 illustrated step-by-step lessons will guide you through all the skills you need to get started. This book includes full-size, fold-out patterns and is the essential guide for all aspiring seamstresses.
Translation of: J'apprends à coudre à la surjeteuse et à la recouvreuse.
In English, translated from the French.
Keywords: Serging; Sewing machines; Machine sewing -- Technique